Factors Influencing Efforts to Prevent DHF in the Community Health Center - Atika, Atika; Nadapdap, Thomson P; Yuniati, Yuniati; Asriwati, Asriwati; Maryanti, Endang (Journal La Medihealtico, 2023)
Dengue hemorrhagic fever (DHF) is an illness spread by the Aedes aegypti mosquito, which is infected with the dengue virus from the genus Flavivirus, family Flaviviridae. The research set out to identify what elements in the Working Area of the Sungai Guntung Public Health Center in the Kateman District of the Indragiri Hilir Regency of Riau were most influential in dengue prevention efforts. An analytical survey using a Cross Sectional Study design is used to conduct the quantitative study. All 19,271 adults living in the nine-village Sungai Guntung Health Center Working Area were included in the analysis. Up to 99 family heads were included in the Stratified Random Sample. Univariate, bivariate, and multivariate analyses were employed to examine the data. Education, knowledge, attitudes, the role of health workers, water storage, and the presence of garbage were all found to be related to efforts to prevent DDB in the Working Area of the Sungai Guntung Health Center in the Kateman District of the Indragiri Hilir Regency of Riau. P = 0.000 0.025, 95% CI = 5.389-316.539, OR = 41.154; the most important factor is level of education. In order to avoid DDB in the Working Area of the Sungai Guntung Health Center in the Kateman District of the Indragiri Hilir Regency of Riau, the study's authors recommend focusing on education, knowledge, attitudes, the role of health professionals, water reservoirs, and the presence of rubbish.